Degredation properties of reinforced concrete walls with openings (2011)
This paper compares the performance of four isolated reinforced concrete (RC) walls with openings: two prototype walls tested under quasi-static cyclic (QSC) loading, and two models tested under shaking table excitation. The variables studied were the web steel ratio, the type of web reinforcement, and the testing method. By means of the measured response, it was verified that loading history of the QSCtesting ignores the foremost dynamic effects observed in structures subjected to earthquake loads. When dynamic and QSC responses werecompared, it was apparent that stiffness and strength degradation properties depend on the loading rate, the strength mechanisms associated to the failure modes, number of cycles, and cumulative parameters such as ductility demand and energy dissipated. We deducted that data obtained from QSC tests cannot always be safely assumed to be a lower limit of the expected capacity. Stiffness and strength degradation models for RC walls with openings subjected to earthquake-type loading are also proposed.